Membrane Rafts in T Cell Activation: A Spotlight on CD28 Costimulation - Zumerle, Sara; Molon, Barbara; Viola, Antonella (Frontiers in Immunology, 2017)
Spatiotemporal compartmentalization of signaling pathways and second messengers is pivotal for cell biology and membrane rafts are therefore required for several lymphocyte functions. On the other hand, T cells have the specific necessity of tuning signaling amplification depending on the context in which the antigen is presented. In this review, we discuss of membrane rafts in the context of T cell signaling, focusing on CD28-mediated costimulation.